2017
DOI: 10.2200/s00807ed1v01y201710icr061
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Context in Information Behavior: Seeker, Situation, Surroundings, and Shared Identities

Abstract: The field of human information behavior runs the gamut of processes from the realization of a need or gap in understanding, to the search for information from one or more sources to fill that gap, to the use of that information to complete a task at hand or to satisfy a curiosity, as well as other behaviors such as avoiding information or finding information serendipitously. Designers of mechanisms, tools, and computer-based systems to facilitate this seeking and search process often lack a full knowledge of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(84 citation statements)
references
References 174 publications
0
79
0
5
Order By: Relevance
“…However, instead of explaining variation in orientation to IB across contexts, much of the earlier model-building tends to be focused on explaining differences in information seeking for distinct purposes and in relation to specific tasks (whether focused tasks-in-hand or general orientation). Several of the existing models acknowledge the significance of contextuality (Agarwal, 2017), but there is both a lack of consensus on what context is (Beyene & Byström, 2017) and an inclination to conceptualize context as something highly unique to a given situation and, even at the same time, as a fairly unspecified external setting of a studied information activity, a perspective that has been criticized for some time (Burnett & Erdelez, 2010;Talja, Keso, & Pietiläinen, 1999). This applies also to collaborative information seeking research, which otherwise addresses the gap between the individual and social aspects of seeking information.…”
Section: Information Behavior and Successmentioning
confidence: 99%
“…However, instead of explaining variation in orientation to IB across contexts, much of the earlier model-building tends to be focused on explaining differences in information seeking for distinct purposes and in relation to specific tasks (whether focused tasks-in-hand or general orientation). Several of the existing models acknowledge the significance of contextuality (Agarwal, 2017), but there is both a lack of consensus on what context is (Beyene & Byström, 2017) and an inclination to conceptualize context as something highly unique to a given situation and, even at the same time, as a fairly unspecified external setting of a studied information activity, a perspective that has been criticized for some time (Burnett & Erdelez, 2010;Talja, Keso, & Pietiläinen, 1999). This applies also to collaborative information seeking research, which otherwise addresses the gap between the individual and social aspects of seeking information.…”
Section: Information Behavior and Successmentioning
confidence: 99%
“…Prior work in this area has found that task problemsolving is the most common information need [47]. Our work suggests displays that show adverse events, results by specific outcomes, and population descriptions by experimental arm match the information processing goals of clinicians seeking research information for medication decision-making.…”
Section: Information Processing Issuesmentioning
confidence: 58%
“…Surveys are easier to administer to a large number of people, which could be the reason why more articles involving data gathering have adopted the survey method. This is also the common trend in most studies in LIS, where surveys are the most popular research method (Agarwal, ). In terms of citation impact, VINE and JIKM are good avenues for LIS‐researchers in the KM area, as these two journals had most of the top‐cited articles.…”
Section: Discussionmentioning
confidence: 86%